Incidence of postoperative acute kidney injury in dogs without pre-existing renal disease - Muñoz-Blanco, Lorena; Salazar, Verónica (Frontiers in Veterinary Science, 2025)
Acute kidney injury (AKI) is defined as a sudden reduction in renal function, characterized by a rapid increase in serum creatinine (sCr) ≥ 0.3 mg/dL within 48 h with or without azotemia (sCr ≥ 1.7 mg/dL) and/or oliguria (urinary output <1 mL/kg/h for more than 6 h). Acute kidney injury is associated with increased mortality, prolonged hospitalization, and higher costs in both human and veterinary medicine. This study aimed to determine the incidence of postoperative AKI in dogs without pre-existing renal disease. A total of 170 dogs, admitted for elective surgery (ASA I-II) at a single university center, were included. The sCr levels were measured at the following times: procedure day (before anesthesia), 24 h, 48 h, and 7 days post-surgery (0 h, 24 h, 48 h, and 7d). Potential risk factors for AKI including patient characteristics (age, sex, pathologies, treatments), anesthetic protocol (drugs, type and rate of fluid therapy, procedure duration) and intraoperative complications were analyzed. Postoperative AKI was identified in 5 dogs (2.9, 95% CI: 1.3–6.7%) based on a sCr increase ≥0.3 mg/dL within 48 h post-surgery. A decrease in sCr (Mean: 0.87 SD = 0.2) was observed at 48 h (Mean: 0.84 SD = 0.24) (p < 0.001), returning to baseline by day 7 (Mean:0.89 SD = 0.22) (p = 0.127). Only a relationship between surgery duration and the probability of developing postoperative AKI was found (p = 0.037). Further studies are warranted to identify risk factors for AKI in dogs undergoing GA and improve its prevention optimizing postoperative management and prognosis.